Genetic consequences of plant edaphic specialization to solfatara fields: Phylogenetic and population genetic analysis of Carex angustisquama (Cyperaceae). Issue 17 (27th December 2019) - Nagasawa, Koki; Setoguchi, Hiroaki; Maki, Masayuki; Goto, Hayato; Fukushima, Keitaro; Isagi, Yuji; Suyama, Yoshihisa; Matsuo, Ayumi; Tsunamoto, Yoshihiro; Sawa, Kazuhiro; Sakaguchi, Shota
Abstract: Edaphic specialization is one of the main drivers of plant diversification and has multifaceted effects on population dynamics. Carex angustisquama is a sedge plant growing only on heavily acidified soil in solfatara fields, where only extremophytes can survive. Because of the lack of closely related species in similar habitats and its disjunct distribution, the species offers ideal settings to investigate the effects of adaptation to solfatara fields and of historical biogeography on the genetic consequences of plant edaphic specialization to solfatara fields. Here, genome‐wide single nucleotide polymorphisms were used to reveal the phylogenetic origin of C. angustisquama, and 16 expressed sequence tag–simple sequence repeat markers were employed to infer population demography of C angustisquama . Molecular phylogenetic analysis strongly indicated that C. angustisquama formed a monophyletic clade with Carex doenitzii, a species growing on nonacidified soil in the sympatric subalpine zone. The result of population genetic analysis showed that C. angustisquama has much lower genetic diversity than the sister species, and notably, all 16 loci were completely homozygous in most individuals of C. angustisquama . Approximate Bayesian computation analysis supported the model that assumed hierarchical declines of population size through its evolutionary sequence. We propose that the edaphic specialist in solfatara fields has newly attained the adaptation to solfatara fields in the process of speciation. Furthermore, we found evidence of a drastic reduction in genetic diversity in C. angustisquama, suggesting that the repeated founder effects associated with edaphic specialization and subsequent population demography lead to the loss of genetic diversity of this extremophyte in solfatara fields.